Trajetória dos acadêmicos indígenas do Instituto de Educação, Agricultura e Ambiente (IEAA) - Ackermann, Rosimeri Barreto (Brasil, 2021)
This work was developed at the Federal University of Amazonas (UFAM) Campus humaitá, in order to approach and interview students who consider themselves indigenous and who are enrolled in the institute, with the thematic trajectory of indigenous academics from the institute of education, agriculture and environment that it emerged through a PIBIC project where a narrative interview was carried out for data collection. This research proposal became very relevant because it provided a critical reflection on the trajectory, difficulties and future perspectives of indigenous students who attend the course at the IEAA/UFAM, in order to provoke debates around indigenous culture.